Comprehensive fingerprint recognition utilizing one shot learning with Siamese Network - Zaman, Sara Milham; Hasan, Md. Abir; Sadat, Md. Rafid; Haque, Md. Abrar (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.